High Input Impedance Voltage-Mode Universal Biquadratic Filters With Three Inputs Using Three CCs and Grounding Capacitors - Horng, Jiun-Wei; Hsu, Chih-Hou; Tseng, Ching-Yao (Společnost pro radioelektronické inženýrství, 2012)
Two current conveyors (CCs) based high input impedance voltage-mode universal biquadratic filters each with three input terminals and one output terminal are presented. The first circuit is composed of three differential voltage current conveyors (DVCCs), two grounded capacitors and four resistors. The second circuit is composed of two DVCCs, one differential difference current conveyor (DDCC), two grounded capacitors and four grounded resistors. The proposed circuits can realize all the standard filter functions, namely, lowpass, bandpass, highpass, notch and allpass filters by the selections of different input voltage terminals. The proposed circuits offer the features of high input impedance, using only grounded capacitors and low active and passive sensitivities. Moreover, the x ports of the DVCCs (or DDCC) in the proposed circuits are connected directly to resistors. This design offers the feature of a direct incorporation of the parasitic resistance at the x terminal of the DVCC (DDCC), Rx, as a part of the main resistance.
Keywords: Current conveyor; biquadratic filter; active circuit